Analysis of Marketing Potential of Regional Typical Products in Taman Mini Indonesia Indah Souvenir Shop - Pradini, Gagih; Kusumaningrum, Anisa Putri; Agustiani, Fitri; Parulian, Sopar; Lestari, Rahayu (CV ODIS, 2023)
The object of this research is the destination of Taman Mini Indonesia Indah. The research area was conducted in East Jakarta City. Data collection was carried out using qualitative methods/interviews with visitors to obtain information related to the marketing potential of regional speciality products at TMII. This study aims to obtain information related to the marketing potential of regional speciality products at TMII. The results of this study indicate that the potential of the souvenir market at TMII or other tourist attractions can be a good means of introducing the culture of each region. Through souvenirs, visitors can learn and appreciate Indonesia's cultural diversity and help connect regions that are far apart